Hydration, fluid regulation and the eye: in health and disease. (19th June 2015) - Sherwin, Justin C; Kokavec, Jan; Thornton, Simon N
Abstract: Variation in systemic hydration status, namely chronic systemic hypohydration or dehydration, can influence the development of several chronic non‐ophthalmic diseases. Owing to the eye's high water content and unique system of fluid regulation, we hypothesized that hydration status may affect the eye in health and disease states. Therefore, we performed a systematic review of the current evidence implicating changes in hydration and their association with ocular physiology and morphological characteristics. We also reviewed relevant clinical correlations of changes in hydration and major common eye diseases. Our findings suggest that systemic hydration status broadly affects a variety of ocular pathophysiologic processes and disease states. For example, dehydration may be associated with development of dry eye syndrome, cataract, refractive changes and retinal vascular disease. On the other hand, excessive hydration is associated with some ocular diseases. Tear fluid osmolarity may be an effective marker of systemic hydration status. Recent studies implicate chronic renin‐angiotensin‐aldosterone system activation in the pathogenesis of diabetic retinopathy and glaucoma but also suggest its antagonism may be a useful therapeutic target. Our findings indicate that assessment of hydration status may be an important consideration in the management of patients with chronic eye diseases and undergoing eye surgery. Further research investigating the role of acute and chronic changes in hydration in individuals with and without ocular disease is warranted.